Innovative Social Work Interventions for Abandoned Children in Cirebon - Muna, Munawaroh; Istiqomah, Istiqomah; Fuad, Anisul (Indonesian Journal of Social Work, 2025)
Cirebon had the highest number of abandoned children in the Ciayumajakuning Region (Cirebon, Indramayu, Majalengka, Kuningan) in 2021, according to data from the Central Statistics Agency (BPS). The number of abandoned children was 662 in Kuningan, 4,515 in Majalengka, 904 in Indramayu, and 5,546 in Cirebon. The purpose of this study was to determine the interventions carried out by social workers at the Cirebon City Social Service in handling neglected children. The research method used was qualitative with a descriptive approach. The results showed that the interventions by social workers in handling neglected children at the Cirebon City Social Service utilized a case management approach. This approach begins with an initial investigation to identify the problems faced by the neglected children, followed by an assessment to further understand these problems using tools such as BPSS (Bio-Psycho-Social-Spiritual). The intervention plan involves referring neglected children who experience physical and psychological abuse to specialists in these fields, such as healthcare professionals and psychiatrists. Social workers wait until the physical and psychological health issues are addressed. The implementation of the intervention involves carrying out the planned referrals. Evaluation is conducted from the initial investigation stage to termination. Referrals are made to other child welfare institutions (LKSA) or the children's families for reintegration. Termination occurs when the neglected child becomes independent or graduates from high school. In their work, social workers at the Cirebon City Social Service also use commonly employed tools and instruments, specifically BPSS (Biological, Psychological, Social, and Spiritual).